Servant Leadership and Perceived Organizational Support for Lecturer Loyalty Through Empowerment - Fitriyana Fitriyana; Henny Widya Astuti; Abdul Rahman; Rini Werdiningsih; Syech Idrus (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
The purpose of this study is to determine whether empowerment can mediate the effects of servant leadership and perceived organization on employee loyalty. This study uses a quantitative approach that consists of two exogenous variables, such as servant leadership and perceived organization, one endogenous variable, namely employee loyalty, and one intervening variable, which is employee empowerment. The data used is primary data obtained directly from respondents, including as many as 143 members of the FPMPI Kopertais 4 association. The research instrument used a Likert scale of 1–5, while the data analysis used SEM diagram analysis, which was processed using Amos Structural Equation Modelling. The results of the study show that servant leadership, perceived organization, and empowerment have a significant effect on employee loyalty directly, while the indirect effect of servant leadership and perceived organization on employee loyalty through employee empowerment has a significant influence. These results indicate that empowerment is able to mediate exogenous and endogenous variables.